Are “Happy” Firms All Alike? A Comparative Analysis of Italian and German Manufacturing Systems - Alessandro Arrighetti; Fabio Landini (Università Di Parma, 2018)
Recent works in the socio-economic and comparative political economy literature suggest the emergence of a predominant neoliberal model of capitalism, which is gradually being adopted by most advanced countries. A similar trend is present in the management literature where competitive advantages are increasingly being associated with a predominant strategic paradigm (integrated global engagement) leaning on the complementarities among R&D, human capital and entry into foreign markets, regardless of the country and industry a firm belongs to. While both views imply a growing tendency towards institutional and strategic homologation, other studies show only a partial convergence in institutional settings and highlight the presence of considerable heterogeneity in managerial conducts. In this paper we explore these contrasting interpretations by comparing the characteristics of manufacturing firms in Italy and Germany. The analysis suggests that (a) independently of the country of origin, globally engaged firms are relatively similar in characteristics that are usually positively correlated with economic performance such as size, age and innovation, but remain highly differentiated in terms of institutions-related variables; b) firms that have not adopted a strategy of global engagement are markedly heterogeneous in terms of both structural characteristics and institutions-related variables. In other words, global engagement is associated with a lower degree of the differentiation between Italian and German firms, but the variety of institutional settings continues to affect the evolution of businesses. Policy implications are discussed.
Keywords: 330; varieties of capitalism; business strategy; global engagement; firm heterogeneity; Italy; Germany